Attitude 2002. - Birnbaum, Daniel; Dadi, Iftikhar; Engberg, Juliana; Gumpert, Lynn; Hassan, Salah; Honda, Yoshiko; Hou, Hanru; Kanazawa, Kodama; Maharaj, Sarat; Minamishima, Hiroshi; Misumi, Yasuyuki; Pejic, Bojana; et al. (Kumamoto : CAMK (Contemporary Art Museum Kumamoto), 2002)
Abramovic, Marina ; BuBu ; Chiezo, Taro ; Endo, Kunie ; Fujioka, Yuki ; Gorlova, Lyudmila ; Gursky, Andreas ; Hori, Kosai ; Ishii, Hiroshi ; Ito, Ryuya ; Itsumo-kokokara ; Ivekovic, Sanja ; Kikuhata, Mokuma ; Kumamoto Yogo School for the mentally impaired ; Kusama Yayoi ; Markovic, Milovan ; Miyajima, Tatsuo ; Nguyen-Hatsushiba, Jun ; Ohara, Yuko ; Okayama, Naoyuki ; Sarkisian, Peter ; Semper, Ene-Liis ; Shimada, Yoshiko ; Shonibare, Yinka ; Shu-min Lin ; Tanaka, Koki ; Tonoshiki, Tadashi ; Turrell, James ; Unit 00 ; Victor, Suzann ; Watanabe, Yoshihiro ; Yanobe Kenji ; Yook, Keunbyung ; Yoshino, Tatsumi
Japans & Engels
Attitude 2002, CAMK (Contemporary Art Museum) Kumamoto, 12.10.2002 - 08.12.2002
boek